PENGARUH SISTEM REKRUTMEN, PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PADA PT SINAR JERNIH SUKSESINDO - Doly Hasiholan Sitompul; Dicky Sinaga; Iren Maruba Sitanggang; Mas Intan Purba (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Work performance and productivity are manifestations of many factors, including satisfaction. Satisfaction is an indirect factor, but its impact is very significant on performance achievement. Even under certain circumstances, job satisfaction becomes the dominant factor in effectiveness, efficiency, and productivity. This study aims to examine the work factors that affect employee job satisfaction. The research method uses quantitative and multiple linear regression analysis. Simultaneous test results show that satisfaction is a factor that is sensitive to company policies, including recruitment, training, and career development. The most interesting thing from this finding is that recruitment is an indirect factor that influences the sense of satisfaction. That is, a good recruitment system can bring a sense of justice to employees, especially at the stage of promotion, clarity in the acceptance of employees in certain positions, is a guarantee of a sense of justice. So there is no more feeling unappreciated or so